Studying and researching with social media - Poore, Megan (Thousand Oaks, CA : SAGE Publications, 2014)
Wondering what your lecturers are looking for in a blog post? Asking yourself how that's different from writing an essay (or a wiki page)? Unsure if Twitter really can be used to build your online profile as a researcher? If you want - or need - to integrate social media tools into your studies and research, this practical book is your one-stop shop. Megan Poore shares the secrets of how to harness the power of social media tools to improve your academic productivity. Inside, you'll find out how to: write a good blog post contribute to a wiki maximise your grades when creating an audio-visual presentation find and share the latest research via Twitter keep safe online. Featuring handy illustrations ...
Description based on MARC record for print version.
Keywords: Social media